Cultivable Actinobacteria First Found in Baikal Endemic Algae Is a New Source of Natural Products with Antibiotic Activity - Denis V. Axenov-Gribanov; Daria V. Kostka; Ulyana А. Vasilieva; Zhanna M. Shatilina; Maria E. Krasnova; Ekaterina V. Pereliaeva; Elena D. Zolotovskaya; Maria M. Morgunova; Olga O. Rusanovskaya; Maxim A. Timofeyev (International Journal of Microbiology)
Inadequate use of antibiotics has led to spread of microorganisms resistant to effective antimicrobial compounds for humans and animals. This study was aimed to isolate cultivable strains of actinobacteria associated with Baikal endemic alga Draparnaldioides baicalensis and estimate their antibiotic properties. During this study, we isolated both widespread and dominant strains related to the genus Streptomyces and representatives of the genera Saccharopolyspora, Nonomuraea, Rhodococcus, and Micromonospora. For the first time, actinobacteria belonging to the genera Nonomuraea and Saccharopolyspora were isolated from Baikal ecosystem. Also, it was the first time when actinobacteria of the genus Nonomuraea were isolated from freshwater algae. Some rare strains demonstrated activity inhibiting growth of bacteria and yeasts. Also, it has been shown that the strains associated with Baikal alga D. baicalensis are active against both Gram-positive and Gram-negative bacteria. According to this study and previously published materials, diversity of cultivable actinobacteria and rare strains isolated from D. baicalensis is comparable to that of cultivable actinobacteria previously isolated from plant sources of Lake Baikal. Also, it exceeds the cultivable actinobacteria diversity previously described for macroinvertebrates, water, or sediments of Lake Baikal. The large number of rare and active strains associated with the endemic alga D. baicalensis could be the promising sources for biopharmaceutical and biotechnological developments and discovery of new natural compounds.